If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 4x + 6 = 14 + -2 Reorder the terms: 6 + -1x + 4x = 14 + -2 Combine like terms: -1x + 4x = 3x 6 + 3x = 14 + -2 Combine like terms: 14 + -2 = 12 6 + 3x = 12 Solving 6 + 3x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 12 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 12 + -6 3x = 12 + -6 Combine like terms: 12 + -6 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 58a+b=cfora | | 13x-3=5x | | 2b-3+6-8=1-b | | x/(x+1)+x/(x-1)=0 | | 2x/5+3=101/2 | | 4m-y=nform | | 12+4x=8x-8 | | 1/2(8-6h)=5 | | 3x^2-12x+24y-48=0 | | 6-4x=7x-9x+4+2 | | C=15f+8h+5p | | 27x-2+47=180 | | 4z+6z=10 | | 27x-2=47 | | 4(x-3)+2=26 | | 7m+n=2forn | | 16x-8=14x+8 | | -3-(2-3x)=2x-(5-x) | | (3x-c)-5=x-7 | | 13-2n=-37 | | a+b(x-y)=cforx | | 20x+10=50 | | 2(x+4)-5(2x-1)= | | 11x-3=10x+5 | | n^2+n=6 | | 12-1.2(x-5)=22-2(5-3s) | | 2x+3/3=x-1/x-2 | | 3+(9n+5)=35 | | 5x+9x+2x+20=52 | | Ax+by=cforx | | n=300 | | 21-(x-5)=-4x+12 |